2015
DOI: 10.3168/jds.2015-9312
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary energy source and level on nutrient digestibility, rumen microbial protein synthesis, and milk performance in lactating dairy cows

Abstract: This study was conducted to examine the effects of dietary energy source and level on intake, digestion, rumen microbial protein synthesis, and milk production in lactating dairy cows, using corn stover as a forage source. Eight multiparous Holstein cows, 4 of which were fitted with rumen cannulas, were evaluated in a replicated 4 × 4 Latin square design, with each period lasting 21 d. The cows were randomly assigned into 4 treatment groups: low-energy (LE) ground corn (GC), LE steam-flaked corn (SFC), high-en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 33 publications
(49 reference statements)
3
27
0
Order By: Relevance
“…In this study, cow fed high RDS TMR had higher fecal nitrogen excretion as a proportion of N intake than cows fed low RDS TMR, which could partly explain the lower total tract apparent digestibility of crude protein of cows fed high RDS TMR than low RDS TMR. The observation that total tract digestibility of DM was not affected by the dietary treatments is consistent with previously reported results [32,33]. Although several studies observed that the digestibility of DM increased when cows were fed more ruminally degradable starch [3,20].…”
Section: Discussionsupporting
confidence: 91%
“…In this study, cow fed high RDS TMR had higher fecal nitrogen excretion as a proportion of N intake than cows fed low RDS TMR, which could partly explain the lower total tract apparent digestibility of crude protein of cows fed high RDS TMR than low RDS TMR. The observation that total tract digestibility of DM was not affected by the dietary treatments is consistent with previously reported results [32,33]. Although several studies observed that the digestibility of DM increased when cows were fed more ruminally degradable starch [3,20].…”
Section: Discussionsupporting
confidence: 91%
“…Milk protein has different types of biological activities, e.g., essential amino acids, growth factors, hormones, enzymes, antibodies, and immune stimulants [1]. An increasing supply of metabolizable protein can increase milk protein yield, and microbial crude protein (MCP) contributes about 40%-60% of metabolizable protein [2,3]. In addition, compared with feed protein, MCP is an excellent source for milk protein production in terms of amino acid contents [4].…”
Section: Introductionmentioning
confidence: 99%
“…The same concentrate was used in both diets (ingredients and chemical composition of the two diets are shown in Table 1) which were fed as a total mixed ration (TMR). Corn stover has a lower nutritional level (Zhu et al 2013), a lower effective degradability in the rumen (Zhou et al 2015), and a lower crude protein content (Saenger et al 1982) than does MFs. Corn stover in…”
Section: Diets Treatments and Experimental Designmentioning
confidence: 99%
“…Changes to the diets of cows can affect the nutrient supply and then affect lactation performance (Boerman et al 2015). The roughage quality in a diet is important to milk synthesis due to its effect on rumen metabolism, thereby influencing the secretion of milk components (Zhou et al 2015). In addition, milk fat, an important component in milk, is sensitive to dietary variations.…”
Section: Introductionmentioning
confidence: 99%